PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA PADA REPUTASI PERUSAHAAN (Studi Empiris pada Perusahaan Travel Umroh dan Haji di Jakarta Timur) - Buddy; Tabroni; Salim, Fahruddin (SEKOLAH PASCASARJANA PRESS, 2019)
Umrah travel business is indeed promising. The best umroh travel will not have a bad track record. This track record shows the quality of service and the level of customer satisfaction. Choose Umrah travel that really has a good reputation where this travel never gets complaints from customers, or problems with third parties. The purpose of this study was to determine the effect of service quality and trust in customer satisfaction and its impact on the company's reputation in Umrah travel in East Jakarta. The study sample was 160 respondents from 5 Umrah travels studied. The sampling technique uses quota sampling, which is that each travel gets a quota of 32 samples. Data collection using a questionnaire. The data analysis technique uses Structural Equation Modeling (SEM) analysis which is processed by LISREL Software. The results of the study prove that service quality variables have a significant effect on customer satisfaction. The trust variable has a significant effect on customer satisfaction. Service quality variables have a significant effect on the company's reputation. While the trust variable does not affect the company's reputation. The customer satisfaction variable has a significant effect on the company's reputation in the Umrah Travel Bureau in East Jakarta.